New versus old: comparison of the 2022 ACR/EULAR versus the 1990 ACR classification criteria for giant cell arteritis in a real-world cohort - Bergner, Raoul; Löffler, Christian; Schulz, P.; Klank, David Karl; Friedrich, Julian (Rheumatology international, 2025)
This study compares the diagnostic performance of the 1990 American College of Rheumatology (ACR) criteria and the 2022 ACR/European League Against Rheumatism (EULAR) classification criteria for giant cell arteritis (GCA), with focus on the complementary roles of MRI and ultrasound imaging.
Online veröffentlicht: 13. Oktober 2025
Gesehen am 08.01.2026